STRATEGI GURU DALAM PENCEGAHAN BULLYING BERBASIS SEKOLAH RAMAH ANAK DI SD NEGERI 1 PRINGKUKU - Giferani, Argin Nisa Bela; Tisngati, Urip; Trisnawaty, Wulan (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2024)
Teacher’s strategy in preventing bullying in elementary schools are crucial factors in creating a safe and conducive learning environment. This study aims to describe teacher strategies for bullying prevention based on a child-friendly school approach at 1 Pringkuku elementary school, employing a descriptive qualitative approach. Data sources includde teachers from grades 1 to 6, with data collected through observation and interviews. The findings indicated that teachers integrate anti-bullying education into subjects such as Indonesian Language and Civic Education, supported by participatory teaching methods and models, the habitual practice of 5S (Senyum, Sapa, Salam, Sopan, Santun), enforcement of rules, and follow-up with educational sanctions and consequences. Additionally, a prevention and violence response team composed of teachers and the school committee has been established to reinforce these efforts. The implementation of teacher strategies based on the child-friendly approach has been highly effective in preventing and addressing bullying at 1 Pringkuku elementary school.